Accountability and challenges of partnership in good governance: Delivering public service - Mohd Yusof, Muhammad Suhaimi; Romle, Abd Rahim; Muhamad Husin, Nur Khairina (ISLAMIC WORLD Network for Environmental Science and Technology (IWNEST Publisher), 2015)
This paper examines the rise of the Partnership Theory in good governance which required collaboration between two or more organizations. The transformation of partnership in governance has led them to have common goals and achievements in delivering public service.However, delivering public service was not as simple as people think due to the challenges in terms of time and energy constraints yet it restraints them from being a part of good governance. Lack of understanding in cooperation and decision making has brought “them” into the challenges created by the partnership itself.Hence, the elements in the partnership should be justified in order to have a clear view on the accountabilities and challenges in maintaining the trust on good governance.Thus, having a better view in partnership roles is crucial in order to strengthen the understanding of the theory in delivering a good public service in the future.